2016
DOI: 10.1007/s10008-016-3301-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonication-polished anodic TiO2 nanotube array-based photoanode for efficient solar energy conversion

Abstract: In this work, the capping layer atop anodic TiO 2 nanotube arrays (NTAs), which hinders filling of other guest materials and transport of charge carriers, is discerned to be TiO 2 nanotapes. Then, it is completely removed by a novel sonication-polishing (SP) treatment, after which Sb 2 S 3 is subsequently introduced to fill the nanotubes by chemical bath deposition. The morphological, structural, and optical properties of the SP-treated TiO 2 NTAs and TiO 2 NTAs/Sb 2 S 3 heterogeneous structures are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…209 It is found that efficient systems can be developed out of a combination of anodization with other synthetic methods for the fabrication of hybrid and multi-layered photoanodes. [210][211][212][213][214][215][216] Another simpler route of TiO 2 nanotube synthesis proposed by Ramakrishnan and co-workers involved the hydrothermal treatment of quasi-crystalline TiO 2 nanoparticles. 217 They were reported to have achieved hydrothermal conditions even without using an autoclave.…”
Section: Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…209 It is found that efficient systems can be developed out of a combination of anodization with other synthetic methods for the fabrication of hybrid and multi-layered photoanodes. [210][211][212][213][214][215][216] Another simpler route of TiO 2 nanotube synthesis proposed by Ramakrishnan and co-workers involved the hydrothermal treatment of quasi-crystalline TiO 2 nanoparticles. 217 They were reported to have achieved hydrothermal conditions even without using an autoclave.…”
Section: Nanotubesmentioning
confidence: 99%
“…Apart from using individual nanotubes, designs involving nanotube arrays were made by certain research groups. 194,204,[206][207][208]210,[212][213][214][215][218][219][220] For example, a highly ordered array of TiO 2 nanotubes with a length of 360 nm was introduced in 2006 by Mor and co-workers with a PCE of 2.9%. 221 This reduction in PCE is due to the comparatively smaller thickness of the photoelectrode.…”
Section: Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…A key figure of merit is the photocurrent density generated by the photoanode under AM1.5G 1 sun illumination (100 mW cm –2 ). Optimized, nanostructured TiO 2 photoanodes are by themselves able to generate 1.2 mA cm –2 under AM1.5G 1 sun illumination at an applied bias of <0.6 V versus NHE through utilization of ultraviolet and blue photons at high Faradaic efficiencies and internal quantum yields . Consequently, any photoanode based on doped TiO 2 or a heterojunction involving TiO 2 needs to significantly outperform the value of 1.2 mA cm –2 to merit serious consideration.…”
Section: Introductionmentioning
confidence: 99%